Improving students' high-level mathematical thinking skills through generative learning models - Moma, La; Tamalene, Hanisa (International Journal of Trends in Mathematics Education Research, 2023)
The purpose of this study was to (1) analyze the achievement of high-level mathematical thinking skills of students who received learning with generative models and learning with conventional models, (2) analyze the increase in students' high-level mathematical thinking skills between those who receive generative learning models and conventional learning models, (3) See the effect of students' KAM (Initial Mathematical Ability) levels in the high, medium, and low categories on the high-level mathematical thinking abilities of students who receive generative learning models and conventional learning models, and (4) The magnitude of the interaction between the generative learning model and the KAM (Initial Mathematical Ability) level of students in the high, medium, and low categories on the improvement of high-level mathematical thinking skills of students who received generative learning models and conventional learning models. This research is experimental with a pretest-posttest control group design. Based on the results of this study, it can be seen that (1) there are differences in the attainment of high-level mathematical thinking skills between students who are taught by generative learning models and conventional learning models, (2) There is a significant difference in the improvement of students' high-level mathematical thinking skills between students who are taught with generative learning models and students who are taught with conventional learning models, (3) For the KAM level of students in the high, medium, and low categories, it does not significantly affect the improvement of high-level mathematical thinking abilities of students who obtain generative learning models and conventional learning models, and (4) There is no interaction between the KAM level (high, medium, or low) and the learning model towards increasing the high-level thinking skills of students who receive generative learning models and conventional learning models